Isolation of Polymorphic Microsatellite Loci in the New Zealand Endemic Sand-Binder, Ficinia spiralis (Cyperaceae) - Heugten, RAV; Hale, ML; Bryan, S; Griensven, BV; Satter, S; Brailsford, L; Buckley, HL (Botanical Society of America, 2017)
Premise of the study: Ficinia spiralis (Cyperaceae) is a declining sand-binding sedge of ecological and cultural importance. Microsatellite primers were developed in F. spiralis to investigate how population genetic structure is related to the pronounced morphological, physiological, and ecological variation observed in this species. Methods and Results: A 454 shotgun-sequencing approach was used to generate 157,274 raw sequence reads, 536 of which contained microsatellites. After initial primer testing for 40 loci, 14 polymorphic loci were isolated, containing five to 27 alleles per locus. Ten of these loci also amplified in a congener, F. nodosa. Conclusions: These loci will enable the assessment of the population genetic structure of F. spiralis, improving our understanding of the population processes underlying the observed morphological, physiological, and ecological variation in this endemic species. As the first microsatellites developed in Ficinia, these loci are a valuable resource for population genetic studies within this genus.
Keywords: Cyperaceae; Ficinia nodosa; Ficinia spiralis; pīngao; polyploidy; microsatellites